2011
DOI: 10.1103/physrevb.83.104515
|View full text |Cite
|
Sign up to set email alerts
|

Excitation spectrum of a two-dimensional long-range Bose liquid with supersymmetry

Abstract: We have studied excitation spectrum of the specfic 2D model of strongly interacting Bose particles via mapping of the many-body Schrodinger equation in imaginary time to the classical stochastic dynamics. In a broad range of coupling strength α a roton-like spectrum is found, with the roton gap being extremely small in natural units. A single quantum phase transition between strongly correlated supefluid and quantum Berezinsky crystal is found.Usually the system of Bose particles at zero temperature exists in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Both the wave function and energy can be explicitly written as a function of the interaction parameter both in homogeneous and trapped geometries [49][50][51][52]. It was observed that a similar construction of the ground state wave function in two dimensions leads to equivalent statistical averages as for a system of classical charges, while the quantum Hamiltonian in addition possesses three-body interaction terms [53][54][55][56].…”
Section: Introductionmentioning
confidence: 99%
“…Both the wave function and energy can be explicitly written as a function of the interaction parameter both in homogeneous and trapped geometries [49][50][51][52]. It was observed that a similar construction of the ground state wave function in two dimensions leads to equivalent statistical averages as for a system of classical charges, while the quantum Hamiltonian in addition possesses three-body interaction terms [53][54][55][56].…”
Section: Introductionmentioning
confidence: 99%